Peningkatan Kemampuan Pengenalan Sejarah Islam melalui Media Screabble Bagi Anak Usia Dini - Adi Priyanto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2018)
The study aims to describe the process and learning achievement through scrabble media to stimulate the students in knowing the history of Islam to kindergarten students age 5-6 years old. The research was an action reseach on group B at TK Nurul Hidayah West Sumatera. The method of the study was Kemmis and Tagart method by applying some steps including planning, action, observation, and reflection. The techniques to collect the data were observation, interview, field noting, instruments of action observer and documentation. The data were analyzed through quantitative and qualitative method. The results in quantitative showed that the students ability at knowing the history of Islam was improved after treated by scrabble. It can be proved by the average of the percentage before treatment was 50.27%. After some treatments in cycle I, it was improved to 69% and it was also improved in cycle II for 85.95%. Based on the result, it can be concluded that scrabble can improve kindergarten students ability at knowing the history of Islam. Krewords: The history of Islam, Scrabble Media